Playing it safe? Managerial preferences, risk, and agency conflicts - Gormley, Todd A.; Matsa, David A. (Journal of Financial Economics, 2016)
This article examines managers’ incentive to play it safe. We find that, after managers are insulated by the adoption of an antitakeover law, they take value-destroying actions that reduce their firms’ stock volatility and risk of distress. To illustrate one such action, we show that managers undertake diversifying acquisitions that target firms likely to reduce risk, have negative announcement returns, and are concentrated among firms with managers who gain the most from reducing risk. Our findings suggest that instruments typically used to motivate managers, such as greater financial leverage and larger ownership stakes, exacerbate risk-related agency challenges.